2018
DOI: 10.1371/journal.pone.0207060
|View full text |Cite
|
Sign up to set email alerts
|

The impact of approaches in improving male partner involvement in the prevention of mother-to-child transmission of HIV on the uptake of safe infant feeding practices by HIV positive women in sub-Saharan Africa. A systematic review and meta-analysis

Abstract: BackgroundThe low level of male partner involvement in Prevention of Mother to Child Transmission of HIV services such as safe infant feeding practices poses a serious challenge to the implementation of guidelines on safe infant feeding and may undermine efforts towards elimination of mother to child transmission of HIV in sub Saharan Africa(SSA). We conducted a systematic review and meta-analysis to identify the approaches that have been utilized to improve male partner involvement in PMTCT services as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The findings of the present study are in line with prior studies that report a significant association between MPI and PMTCT outcomes. A series of systematic reviews examining studies from sub‐Saharan Africa by Takah et al 13,18‐20 indicated that MPI in PMTCT—typically conceptualized as a single isolated behavior such as male attendance at ANC—is associated with women's uptake of ART during pregnancy, 13 facility delivery, 18 safe infant feeding, 19 and uptake of infant HIV prophylaxis 20 . In a prospective cohort study, Aluisio et al 21 further found that MPI in PMTCT in the form of ANC attendance in Kenya resulted in increased HIV‐free survival of infants throughout the first year of life.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study are in line with prior studies that report a significant association between MPI and PMTCT outcomes. A series of systematic reviews examining studies from sub‐Saharan Africa by Takah et al 13,18‐20 indicated that MPI in PMTCT—typically conceptualized as a single isolated behavior such as male attendance at ANC—is associated with women's uptake of ART during pregnancy, 13 facility delivery, 18 safe infant feeding, 19 and uptake of infant HIV prophylaxis 20 . In a prospective cohort study, Aluisio et al 21 further found that MPI in PMTCT in the form of ANC attendance in Kenya resulted in increased HIV‐free survival of infants throughout the first year of life.…”
Section: Discussionmentioning
confidence: 99%
“…Men in Botswana regarded antenatal care (ANC) facilities as being "generally unfriendly" to them [ 9 ]. Most recently, a review of studies incorporating men suggested that male "support" as well as "involvement" are key to increasing PMTCT uptake [ 10 ]. The WHO 2010–2015 guidelines on PMTCT emphasize the need to involve male partners to scale up PMTCT services in sub-Saharan Africa [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…While ensuring better coverage of ART for pregnant women, numerous systematic reviews interventions targeting factors that may influence their use of prevention of mother-to-child transmission (PMTCT) services are complementary to help reduce MTCT more quickly (Ambia & Mandala, 2016;Mutabazi et al, 2017; Organisation mondiale de la santé (OMS), 2013; Wettstein et al, 2012). Among these interventions, the involvement of pregnant women's partners in antenatal care and PMTCT has identified that it can improve outcomes of PMTCT programs in resource-limited settings such as uptake and adherence to ART during pregnancy and delivery, enhancement of HIV-free survival among children (Dunlap et al, 2014;Frederick Morfaw et al, 2013;Manjate Cuco et al, 2015; Organisation mondiale de la santé (OMS), 2012; Takah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%